2023
DOI: 10.1021/acsmacrolett.3c00043
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Olefin Terpolymers with High Refractive Index and High Optical Transparency

Abstract: Cyclic olefin copolymer (COC) is one of the most promising optical materials; however, the brittle COC suffers from issues including a low refractive index. In this contribution, by the introduction of high refractive index comonomers including phenoxy substituted α-olefin (C 4 OAr), p-tolylthio substituted α-olefin (C 4 SAr) and carbazolyl substituted α-olefins (C 4 NAr, C 3 NAr, and C 2 NAr), the zirconocene mediated terpolymerization of ethylene (E) and tetracyclododecene (TCD) produces the preferred E-TCD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…The latter leads to production of COCs, which are attractive engineering plastics with high performances, including high transparency in the ultraviolet–visible (UV–vis) region (amorphous material), good thermal resistance (high T g ), and extremely low water absorption (excellent water vapor barrier properties) . Many catalytic systems, such as conventional metallocene, constrained geometry catalyst (CGC), , nonbridged half-titanocene, and nonmetallocene, , have been reported for the copolymerization of ethylene with cyclic olefins, especially with norbornene (NBE). However, successful catalysts that can produce COCs with random structures, high molecular weights ( M w s), narrow distributions, and high T g values (high NBE contents) are still limited …”
Section: Introductionmentioning
confidence: 99%
“…The latter leads to production of COCs, which are attractive engineering plastics with high performances, including high transparency in the ultraviolet–visible (UV–vis) region (amorphous material), good thermal resistance (high T g ), and extremely low water absorption (excellent water vapor barrier properties) . Many catalytic systems, such as conventional metallocene, constrained geometry catalyst (CGC), , nonbridged half-titanocene, and nonmetallocene, , have been reported for the copolymerization of ethylene with cyclic olefins, especially with norbornene (NBE). However, successful catalysts that can produce COCs with random structures, high molecular weights ( M w s), narrow distributions, and high T g values (high NBE contents) are still limited …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the resulting polymer has a surprising Abbe number, which is the highest reported in recent years. As shown in Figure c, the high- v (>30) materials and commercial products (PMMA, PC, CR-39, COC, and MR-8) in recent years are compared. ,,,, ,, P­(DMMD-P) and P­(DEMD-P) are in the yellow area above the middle, which achieves an Abbe number of 59 while maintaining a refractive index of 1.60. This is because the special heterocycle structure of the monomer and the ester bond in the polythiols endow the material with an extremely high Abbe number.…”
Section: Resultsmentioning
confidence: 99%
“…Although the mentioned sulfur-containing polymers can easily achieve a high- n above 1.60, the abundant aromatic rings in the molecular structure also bring high atomic dispersion (Δ R ), thus exhibiting a relatively low Abbe number (less than 50). Recent studies have shown that cyclic olefins and sulfur-containing alicyclic groups have a lower Δ R than aliphatic groups . In particular, the cyclic olefin copolymers (COCs) prepared from norbornene have developed rapidly in the past decade, which have a high- v and high optical transparency. However, the disadvantage of COC materials is that the n value is relatively low (1.52–1.54) and it is difficult to regulate to achieve enhancement. Similarly, norbornadiene has great potential in endowing sulfur polymers with interesting optical and mechanical properties owing to the inherent bearing of the unique aliphatic rigid structure. Hence, based on the excellent optical properties of norbornene, the design of optical materials with high- n and high- v has important research significance and great commercial value.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, combining a polymer of high mechanical strength with a silica framework can potentially achieve reinforcement with minimal impact on the size and stacking of secondary particles. Cyclic olefin copolymers are particularly noteworthy for their high mechanical strength and modulus. The copolymerization of norbornene and ethylene with 46.5 mol % of cyclic olefin yields a brittle material with a remarkable tensile strength of 47.8 MPa and compressive modulus of 2580 MPa …”
Section: Introductionmentioning
confidence: 99%